Humanities Research Centre : a history of the first 30 years of the HRC at the Australian National University - Barclay, Glen St. John, 1930- (ANU E Press, 2004)
A history of the HRC at the ANU, but also an examination of the role and predicament of the humanities within universities and the wider community, and contributes substantially to the ongoing debate on an Australian identity.